Підсумки інтродукції рослин на ботаніко-географічній ділянці “Степи України” Національного ботанічного саду ім. М.М. Гришка НАН України - Gritsenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The results of the introduction of plants in the botanical- geographic plot site "Steppes of Ukraine" in M.M. Gryshko National Botanical Gardens of the NAS of Ukraine are summed up. The efficiency of preservation of the floristic diversity of the steppes of Ukraine ex situ is substantiated.